Indonesian-English Machine Translation Using Rule-Based Method - Novi Yusliani; Yunita Yunita; Wenty Octaviani (Annual Research Seminar (ARS), 2015)
Rule-Based Machine Translation (RBMT) used a set of linguistic information to translate source language to target language. POS tagger and Shift-Reduce-Parsing (SRP) could be used to get the linguistic information. POS tagger was used to get word class of each word in sentence and SRP was used to get the function of each word in sentence. SRP was also used to get the structure of sentence. In this research, POS tagger and SRP were used to get the linguistic information of source sentence. Translation process was done by using billingual dictionary. Last, a set of rules was used to generate the target sentence. The accuracy of Indonesian-English machine translation was 100% for the S-P-Adv pattern, but for the S-P pattern and S-P-O pattern is 93,33%.